Growth and nitrogen uptake by Arthrospira platensis cultured in aquaculture wastewater from Nile tilapia reared in biofloc system (Acta Scientiarum. Biological Sciences, 2021)
This study aimed to evaluate the growth of Arthrospira (Spirulina) platensis cultivated in Zarrouk culture medium and effluent from Nile tilapia (Oreochromis niloticus) reared in biofloc system. Four treatments were used: Control (100% Zarrouk), E50 (50% Zarrouk + 50% Tilapia effluent), E75 (25% Zarrouk + 75% Tilapia effluent), and E100 (100% Tilapia effluent), and the experiment lasted 10 days. Growth parameters such as maximum cell density (MCD), doubling time (DT), and growth rate (K) were daily evaluated, as well as pH and water temperature. In addition, the concentrations of total ammonia nitrogen (TAN), nitrite-N (NO2-N), and nitrate-N (NO3-N) were analyzed in order to compare nitrogen absorption. Among treatments, E50 and E75 obtained higher maximum cell densities and presented an exponential growth rate similar to the control treatment. Regarding the concentrations of nitrogen compounds, a significant reduction was observed in all treatments, with an NO3-N uptake of 99%, followed by 80% of TAN and 90% of NO2-N. Thus, giving the results obtained, besides being able to grow in wastewater, A. platensis can also be used in bioremediation processes, confirming the potential of this species.